Усовершенствование контура регулирования мощности газовой турбины когенерационной энергетической установки в условиях изменения качества топлива - Тарахтий, О.С. (Проблемы управления и информатики, 2017)
Проведено аналіз впливу зміни низької теплоти згорання палива на динамічні характеристики когенераційної енергетичної установки. Вдосконалено контур регулювання потужності ГТУ шляхом введення додаткового сигналу за похідною температури газів на виході камери згорання. Представлено результати комп’ютерного моделювання. The analysis of influence of change of net calorific value of the fuel on the dynamic characteristics of the cogeneration power plant is performed. Control loop for power gas-turbine installations is improved by means of introduction of additional signal derived by the temperature of the gases at the outlet of the combustion chamber. The results of computer simulation are presented.